O12: IHC ANALYSIS OF RESIDUAL DISEASE POST NEOADJUVANT TRASTUZUMAB FOR EARLY STAGE BREAST CANCER REVEALS ER/HER2 CROSSTALK THROUGH INCREASED ER SIGNALLING. (27th April 2021) - Flanagan, M; Varšlija, D; Charmsaz, S; Purcell, S; Cosgrove, N; Cocchiglia, S; Bane, F; Sheehan, K; Hill, AD; Young, LS
Abstract: Introduction: Therapeutic pressure functionally affects oncogenes and related signalling pathways through dynamic alterations in transcriptional and epigenetic alterations. Altered receptor status occurs throughout tumour progression and may be influenced by adjuvant and neoadjuvant therapies. Recurrent transcriptional remodelling events have been described in the progression of primary breast cancer to metastasis, including increased tyrosine kinase signalling, specifically Her2, and loss of ESR1 gene expression. We hypothesise that in the setting of tyrosine kinase inhibition, an increase in estrogen receptor (ER) signalling is observed. Method: A database of patients recruited to ICORG trial 07/09 was queried to identify patients with histologically confirmed, Her2‐overexpressing or Her2 amplified, nonmetastatic, invasive breast cancer who received neoadjuvant trastuzumab,  alone or in combination with neoadjuvant systemic chemotherapy. Clinicopathological characteristics recorded include age at diagnosis, clinical stage,  receptor status and percentage positivity, and pathological complete response. Result: A total of 55 patients identified on ICORG trial 09/07 received neoadjuvant trastuzumab. Of these, 27 achieved a complete pathological response (49%; n=27/55). In those with residual disease, a gain in mean ER staining percentage positivity was observed in the residual disease compared to diagnostic biopsy staining (59.22 vs 45.11; p=0.03). A corresponding loss in Her2 percentage staining positivity was also observed (p=0.006). Conclusion: An inverse correlation was observed between loss of Her2 positivity and percentage gain in ER staining in patients with residual disease following treatment with neoadjuvant trastuzumab. Further study is needed to elucidate the regulatory mechanism of ER/Her2 crosstalk, which may be epigenetically regulated through DNA methylation. Take‐home message: ER/Her2 crosstalk can be demonstrated clinically in IHC analysis of patients with residual disease post neoadjuvant trastuzumab. Tyrosine kinase inhibition in the form of neoadjuvant trastuzumab results in loss of Her2 signalling and corresponding gain in ER signalling.